Railway track width gauge performance review: evaluation of test results and their implications for safety improvement - Prasetyo, Febrian Angga; Sunarto, Setio Aji; Suprijanto, Suprijanto; Gunawan, Leonardo (Jurnal Nasional Aplikasi Mekatronika, Otomasi dan Robot Industri (AMORI), 2024)
The deteriorated state of the railway line poses operational risks for railway transportation due to potential safety concerns. The train derailment occurred because of an abnormal track width that was not immediately repaired. This improvement was omitted because of the absence of an accurate and real-time track width measurement tool. Several gauge have been widely developed. The measuring instrument developed uses an LMP (Linear Motion Position) sensor to measure the width of the path. The measuring mechanism connects the LMP shaft to a roller bearing arm that can move linearly and dynamically according to the groove width of the path. The linear movement of the roller bearing with the arm connected to the LMP shaft is converted as a change in the path width. To determine the function and measurement results of the measuring instrument, measurement experiments were conducted at Sidotopo stations (lines 5 and 6). Line 5 was chosen because of the straight area of the money order needle, the parallel crossing groove, and the curve. Line 6 was chosen because there is a gongsol path. Measurements on each path are made twice with the starting point and opposite direction. The measurement data are shown in the form of a width graph to the distance with one red line as the tolerance limit for widening the width of the line (1074 mm) and one blue line as the tolerance limit for narrowing the width of the line (1065 mm). The measurement results show the consistency of the measurement results. The largest measured width condition is 1092 mm, and the smallest measured width condition is 1058 mm.